Design Considerations For Dual Winding Permanent Magnet Synchronous Machines - Mese, E.; Tezcan, M.; Ayaz, M.; Yasa, Y.; Yilmaz, K. (IEEE, 2012)
This paper presents design and analysis performed for a dual winding electric machine. Windings of the machine are concentrated type so that electrical and magnetic isolation is maintained. For this reason, the proposed structure could be a reasonable candidate for fault tolerant applications. As required by some applications (electric accessory drive system (EADS) for hybrid electric vehicles), simultaneous motoring and generating operations can be implemented in a single housing of electric machine. Design considerations of the proposed electric machine are outlined in the paper. Also a comparison between distributed winding topology and concentrated winding topologies is performed. Finally experimental results discussed.
Keywords: Permanent Magnet Synchronous Machine; Concentrated Winding; Dual Winding Electric Machine; Fault Tolerant Operation; Hybrid Electrical Vehicle Application; Engineering